The influence of financial behaviour on financial risk tolerance in investment decision: A conceptual paper - Bunyamin, Mubarokah; Abdul Wahab, Norwazli (Penerbit Universiti Malaysia Pahang, 2022)
There is a growing stream of research to seek for a solution to improve financial risk tolerance (FRT) in investment decisions, which is most likely conducted from financial institutions and was revealed that there are varieties of factors contribute to this aspect. The literature demonstrated that FRT is considered as the powerful factor that encourages investors’ intentions towards investments. Study shows that the FRT can be improved through positive financial behaviour. Hence it is essential to explore financial behaviour and FRT influences in investment decision from studies around the world and Malaysian market. Therefore, this wide discussion will benefit financial practitioners and institutions in financial practices. In addition, this study surely contribute some additional insights towards existing literature.